Strategi Implementasi Logistik di Instalasi Farmasi Rumah Sakit - Nurul Aini; Kania Rizqita Dewi; Ummi Rahma; Faza Duta Pramudyawardani; Sarah Rania Annisa; Safina Annajah; Acim Heri Iswanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
In hospital pharmacy installations, strategic logistics management has a very important role in terms of drug supply because of its routine and periodic nature. Researchers utilize various literature that is related and relevant to research as a source to obtain data. In obtaining sources for this research literature study, the authors conducted a search from selected databases such as Google Scholar that matched the research topic using the keywords logistics management, pharmaceutical installations, and strategy. At the input step, a condition evaluation is performed using value factors that apply as input to logistics management at pharmaceutical installations in hospitals, which may be analyzed with 5M. To eliminate or reduce unintended bias, inventory selection and assessment must be done properly and according to a strategy. Even after carrying out and applying standards to the input factor availability strategy and the processing process, logistics availability difficulties still arise often. This might happen owing to the effect of unknown variables. The process of implementing logistics management at pharmaceutical installations in several hospitals has been carried out well when viewed from the 5M management factor (man, money, material, machine, and method). SIMRS, or Hospital Management Information System, is utilized by hospitals as a pharmaceutical information system, which is highly significant and beneficial in creating reports connected to medication supplies; yet, there are hospitals where the information systems are not used efficiently. Standard Operating Procedures (SOP) are used to manage pharmaceutical installations in hospitals, although there are still flaws in their implementation.